2007
DOI: 10.1377/hlthaff.26.2.409
|View full text |Cite
|
Sign up to set email alerts
|

Health At School: A Hidden Health Care System Emerges From The Shadows

Abstract: A vast array of child health professionals-99,000 counselors; 56,000 nurses; 30,000 school psychologists; 15,000 social workers; and smaller numbers of dental hygienists, dentists, physicians, and substance abuse counselors-provide care to children and adolescents at school. However, most thought leaders in child health know little about this "hidden" system of care or are skeptical about its capacity to contribute to children's well-being. Increased interest in prevention and chronic disease management, power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 2 publications
0
68
0
1
Order By: Relevance
“…While these SBHCs may not be the primary care provider due to their seasonal nature or operation during school hours only, they can function as a coordinated medical home with the primary care provider for most chronically ill children. 3 The SBHC can monitor and ensure proper maintenance regimes for the child, reducing more expensive, acute care. 8,9,31 In fact, Guo et al found that two different subsets of chronically ill children enrolled in Medicaid with access to an SBHC-one set with asthma and one set with mental health problems-had lower hospitalization and emergency room costs than Medicaid-enrolled children with no SBHC access.…”
Section: Discussionmentioning
confidence: 99%
“…While these SBHCs may not be the primary care provider due to their seasonal nature or operation during school hours only, they can function as a coordinated medical home with the primary care provider for most chronically ill children. 3 The SBHC can monitor and ensure proper maintenance regimes for the child, reducing more expensive, acute care. 8,9,31 In fact, Guo et al found that two different subsets of chronically ill children enrolled in Medicaid with access to an SBHC-one set with asthma and one set with mental health problems-had lower hospitalization and emergency room costs than Medicaid-enrolled children with no SBHC access.…”
Section: Discussionmentioning
confidence: 99%
“…Support mostly comes from the federal government, private and public foundations, Medicaid, health insurance companies, and the Healthy Schools/Healthy Communities program of the Bureaus of Primary Health and Maternal and Child Health. 45 NASBHC has been instrumental in trying to address funding and has suggested that SBHC services should be covered by SCHIP under Medicaid or related MCOs. [46][47][48][49] Prevention of costly mental health problems not only has economic implications but also important societal benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, public contexts such as schools, hospitals, places of employment, etc. should be regarded as active partners in the construction of an equal and fair society that promotes a better quality of life for people with a chronic disease (Stainton, 2005;Lear, 2007), and as instrumental to their autonomy, well-being and empowerment.…”
Section: The Chronic Illness Life Experience From An Ecological Perspmentioning
confidence: 99%